SAE Technical Paper Series 2003
DOI: 10.4271/2003-01-3245
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur Management of NOx Adsorber Technology for Diesel Light-duty Vehicle and Truck Applications

Abstract: Sulfur poisoning from engine fuel and lube is one of the most recognizable degradation mechanisms of a NO x adsorber catalyst system for diesel emission reduction. Even with the availability of 15 ppm sulfur diesel fuel, NO x adsorber will be deactivated without an effective sulfur management. Two general pathways are currently being explored for sulfur management: (1) the use of a disposable SO x trap that can be replaced or rejuvenated offline periodically, and (2) the use of diesel fuel injection in the exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…This result indicates the preferential sulfatization of potassium in comparison to cerium and manganese, as no peaks corresponding to manganese or cerium sulfate were observed. This finding is also in agreement with literature data on SO 2 storage on alkali metal containing compounds [18,19].…”
Section: Resultssupporting
confidence: 83%
“…This result indicates the preferential sulfatization of potassium in comparison to cerium and manganese, as no peaks corresponding to manganese or cerium sulfate were observed. This finding is also in agreement with literature data on SO 2 storage on alkali metal containing compounds [18,19].…”
Section: Resultssupporting
confidence: 83%
“…One strategy is to prevent SO x from reaching the NSC by including a, so-called, sulfur trap upstream the NSC in the aftertreatment system. Two different types of upstream sulfur traps have been proposed earlier, i.e., disposable [3] and regenerable [5]. Here, the latter is considered to be used under continuously lean conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Tests have shown that NACs suffer a loss in conversion efficiency when exposed to high-temperature, lean-rich conditions. This loss becomes greater as temperature increases [4]. Emissions before desulfurization at 300 hours showed a steep increase in NO x .…”
Section: Fresh-catalyst Effectsmentioning
confidence: 99%